Pengaruh Disiplin Kerja dan Beban Kerja terhadap Kinerja Pegawai - Atika Putri, Tiara; Efendi, Achmad; Damingun, Damingun (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the extent to which work discipline and workload influence employee performance at the Regional Inspectorate of East Kalimantan Province. The research employs a quantitative approach using multiple linear regression analysis. The results indicate that both work discipline and workload have a positive and significant impact on employee performance, both partially and simultaneously. Work discipline contributes to the creation of a productive work environment, while a proportional workload enhances focus and work effectiveness. The research model explains 66.4% of the variation in employee performance. These findings highlight the importance of systematic human resource management.